Participation Of The Al-Munawaroh Muslimat Ta'lim Community Channel 7 In Building Religious Social Attitude Relations In The Community - Supianun; Erwin; Sukino (IJGIE (International Journal of Graduate of Islamic Education), 2023)
The research of the Al Munawaroh Muslimat Council of Ta'lim Line 7 Laman Bukit Village has the advantage that it is a place for community development that requires spiritual cleansing. This type of research is qualitative with a Grounded Theory Research approach to data sources from leaders, village heads, RT heads and members of the Ta'lim Al Munawaroh Muslimat Assembly Line 7 Laman Bukit Village. Data collection techniques using interview techniques, non-participant observation and documentation. Data analysis; data reduction, data display, conclusion and verification. The results of this study concluded: 1) Forms of Participation of the Ta'lim Al Munawaroh Muslimat Council Pathway 7 in Developing Relations of Social Religious Attitudes of the Laman Bukit Village Community, namely routine recitation every Friday at noon, increasing congregational prayer activities, encouraging community cohesiveness in recitation, collective dhikr, as well as fostering how to build an Islamic family that is tolerant towards each other is shown by helping each other, accepting differences and making donations to mosques, prayer rooms, poor families, and orphans in every activity held 7 Developing Relationships with Religious Social Attitudes of the Laman Bukit Village Community, namely changing mindsets, changing ways of dressing and attitudes in the process of social interaction, a sense of solidarity between communities in helping people who are less fortunate, establishing friendship among people